A Study on the Relationship of Artificial Intelligence Applications in HR Processes for Assessing Employee Engagement, Performance, and Job Security - Malik, Azam (International Review of Management and Marketing, 2024)
The objective of this research is to investigate how artificial intelligence (AI) might improve HR procedures and increase employee engagement and productivity in organizations. AI-powered tools and applications used in the current era become a decisive point for businesses and its performance may impact employees’ job engagement and job performance. The use of artificial intelligence in an organization’s activities to manage human resources in the areas of employee engagement, job security, employee performance, particularly in the process of lowering staff workload, and enhancing business performance. The study involved full-time employees with experience using artificial intelligence powered software in Indian multinational corporation. The research data was collected from 310 employees from multinational cooperation. The findings demonstrate that artificial intelligence performance had a significant impact on employee’s performance and job engagement, both of which were highly correlated with performance at work evaluation. AI has a positive impact on employee engagement and company performance. Artificial intelligence and job performance were significantly related with job engagement and service performance. Additionally, job security had a significant impact on increasing employees’ job engagement and service quality. The study’s implication support strategies for conducting performance research and managing human resources. The present study results will help business owners or managers create a productive atmosphere that boosts overall performance and employee engagement at the workplace using artificial intelligence.